Enhanced growth and photosynthetic efficiency in wild rocket (Diplotaxis tenuifolia L.) following multi-species microalgal biostimulant application - Mollo, Lorenzo (Plant science : an international journal of experimental plant biology, 2025)
Copyright © 2025 The Authors. Published by Elsevier B.V. All rights reserved.